Пошаговое объяснение:
2/3х + 4/9х = 3,2
6/9х + 4/9х = 32/10
10/9х = 32/10
х = 32/10 : 10/9
х = 32/10 * 9/10
х = 16/5 * 9/10
х = 144/50
х = 2 44/50
х = 2 22/25 или 2,88
х - 0,2х = 8/15
0,8х = 8/15
8/10х = 8/15
х = 8/15 : 8/10
х = 8/15 * 10/8
х = 1/3 * 2/1
х = 2/3
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Пошаговое объяснение:
2/3х + 4/9х = 3,2
6/9х + 4/9х = 32/10
10/9х = 32/10
х = 32/10 : 10/9
х = 32/10 * 9/10
х = 16/5 * 9/10
х = 144/50
х = 2 44/50
х = 2 22/25 или 2,88
х - 0,2х = 8/15
0,8х = 8/15
8/10х = 8/15
х = 8/15 : 8/10
х = 8/15 * 10/8
х = 1/3 * 2/1
х = 2/3